2006
DOI: 10.1124/jpet.105.100594
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Cocaine with Dopamine Uptake Inhibitors or Dopamine Releasers in Rats Discriminating Cocaine

Abstract: Several dopamine (DA) indirect agonists have been proposed as potential medications for treating cocaine abuse. The objective of the present study was to quantify the interactions among cocaine and DA uptake inhibitors or DA releasers to better understand how these drugs may be working when administered in combination. The DA uptake inhibitors GBR 12909 [1-{2-[bis-(4-fluorophenyl)methoxy]-ethyl}-4-(3-phenylpropyl)piperazine], WIN 35,428 [2␤-carbomethoxy-3␤-(4-fluorophenyl)tropane], methylphenidate, indatraline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 35 publications
4
37
0
Order By: Relevance
“…Once induced, the reinforcing effects of the selective s 1 R agonists were independent of dopaminergic mechanisms in this study as well as a previous study (Hiranita et al, 2013). The lack of substantive dopaminergic mediation of the effects of sR agonists is not surprising in light of behavioral studies showing a failure of the sR agonists, PRE-084 or DTG, to substitute for cocaine in rats trained to discriminate cocaine from saline injections (Hiranita et al, 2011b), a procedure in which a number of indirect dopaminergic agonists fully substitute for cocaine (Witkin et al, 1991;Li et al, 2006). Furthermore, administration of intravenous doses of PRE-084 that maintained self-administration behavior did not significantly stimulate dopamine levels in the nucleus accumbens shell in rats that had self-administered cocaine and PRE-084, or in rats that were not previously exposed to cocaine or PRE-084 (Hiranita et al, 2010(Hiranita et al, , 2013Garcés-Ramírez et al, 2011).…”
Section: Discussionmentioning
confidence: 77%
“…Once induced, the reinforcing effects of the selective s 1 R agonists were independent of dopaminergic mechanisms in this study as well as a previous study (Hiranita et al, 2013). The lack of substantive dopaminergic mediation of the effects of sR agonists is not surprising in light of behavioral studies showing a failure of the sR agonists, PRE-084 or DTG, to substitute for cocaine in rats trained to discriminate cocaine from saline injections (Hiranita et al, 2011b), a procedure in which a number of indirect dopaminergic agonists fully substitute for cocaine (Witkin et al, 1991;Li et al, 2006). Furthermore, administration of intravenous doses of PRE-084 that maintained self-administration behavior did not significantly stimulate dopamine levels in the nucleus accumbens shell in rats that had self-administered cocaine and PRE-084, or in rats that were not previously exposed to cocaine or PRE-084 (Hiranita et al, 2010(Hiranita et al, , 2013Garcés-Ramírez et al, 2011).…”
Section: Discussionmentioning
confidence: 77%
“…Further, in this and previous studies (Hiranita et al, 2011b;Martin-Fardon et al, 2007), selfadministration of cocaine was insensitive to pretreatment with s 1 R antagonists, whereas the self-administration of the s 1 R agonist, PRE-084, in the present study was dosedependently blocked by s 1 R antagonists. A lack of substantive dopaminergic mediation of the effects of sR agonists is further supported by a failure of either PRE-084 or DTG to substitute for cocaine in rats trained to discriminate cocaine from saline injections (Hiranita et al, 2011a), a procedure in which a number of indirect dopaminergic agonists fully substitute for cocaine (Li et al, 2006;Witkin et al, 1991). Importantly, the cocaine-discrimination procedure involves regular cocaine injections, further indicating that administration of cocaine alone does not induce pharmacological responses to sR agonists similar to those of cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that the discriminative effects of cocaine can be potentiated by DA uptake inhibitors, both "standard" inhibitors that did (Holtzman, 2001;Li et al, 2006) and those that did not (Tolliver et al, 1999;Katz et al, 2004) fully substitute for cocaine. The present compounds enhanced rather than antagonized the discriminative stimulus of cocaine.…”
Section: Discussionmentioning
confidence: 99%